A study of accelerator driven sub critical system - material using the CASCADE code - Kumar, V.; Kumawat, H.; Chitra Bhatia (Вопросы атомной науки и техники, 2009)
In the existing situation of experimental data required for design and modeling of ADS and similar other applications, development and benchmarking of the simulation codes for providing reliable data has become essential. Amongst the intra nuclear cascade codes, CASCADE code which has been validated for the neutron production in proton collision with the high Z materials in the past, has been used to study nuclear behavior of some of the prominent ADS materials like, Th, U, Pb, Bi, W, Fe, Cr and Al in respect of reaction and production cross sections of isotopes and neutrons in a wide range of energy, 11 MeV to several GeV. Emphasis has been laid on the data of cross sections of (n, xn) reactions. It is found that their role is definite and effective in deciding fuel combinations. The code provides neutron cross section data which shows agreement with the existing experimental data and stresses need of further validation using precision data from the accelerators.